Audiovisual-Based Education to Enhance Digital Health Literacy and Dental Health Behaviors at SDN 1 Sumberejo - Tri Wiyatini; Arief Azhari Ilyas; Rozikhan; Ichsan Rizqi Dewanto (Jurnal Pengabdian Masyarakat Lentora, 2026)
Low digital health literacy among elementary school students in rural areas remains a significant barrier to independent dental and oral health maintenance. This issue was identified at SDN 1 Sumberejo, Kendal, where students had not utilized digital technology for health information and possessed minimal dental health knowledge. This community service program aimed to empower students by enhancing their digital health literacy and improving dental health behaviors through an audiovisual-based educational approach. The intervention was conducted on August 12, 2025, involving 20 students, with implementation stages including: problem identification through surveys, interactive education using creative videos, demonstrations of proper tooth-brushing techniques, and direct guidance in accessing digital health applications. The results showed a positive transformation, with all students now capable of independently operating health information applications. The final evaluation recorded a significant increase in understanding, with all participants (100%) achieving the established competency standards (scores above 75%). This activity successfully built new awareness and provided practical skills for students to leverage technology for maintaining dental and oral health, thereby fostering sustainable healthy lifestyles within the school environment.